The Effects of Activating the Money Concept on Perseverance and the Preference for Delayed Gratification in Children - Trzcińska, Agata; Sekścińska, Katarzyna (Frontiers in Psychology, 2016)
The psychological model of thinking about money assumes that implicit reminders of money lead to self-sufficient motivation. Previous research has demonstrated that children react to money in similar ways to adults. The priming of young children with money related concepts or images has negatively affected their social behaviour and social preferences, leading them to make more individualist and less pro-social choices and be less willing to help others. The aim of this research was to investigate the positive influence of money activation on children’s behaviour. The participants were six to eight year old children who do not yet fully understand the instrumental function of money due to their young age. Two experimental studies were performed, the first of which analysed the effect of perseverance and performance on a challenging task and the second investigated preferences with respect to delaying gratification. Sixty-one children aged 6 took part in the first study and forty-six scout camp participants 6 to 8 years of age were involved in the second experiment. The results support the hypotheses concerning the effects of money activation stating that (1) money activation influences children’s perseverance and effectiveness in difficult individual tasks, and that (2) it increases children’s preferences for delayed gratification. These results suggest that money has a symbolic power which may exert both positive and negative effects on children’s behaviour. Since children between the ages of 6 and 8 do not understand the instrumental function of money fully, certain symbolic meanings of money may have been responsible for the money priming effects. The findings suggest that the symbolic function of money is more primal than its instrumental function and that it probably develops at an earlier stage in life.